Non-mycobacterial CNS infection: Approach to diagnosis (Bangladesh Journal of Medicine, 2024)
Non-mycobacterial CNS infection includes some viral, pyogenic, fungal and parasitic infections in the CNS. Recently, we encountered the COVID-19 pandemic and the outbreak of dengue fever in Bangladesh. Both of the diseases had several central nervous system (CNS) manifestations. In the post-COVID period we are encountering increasing deep fungal infections. In the case of Dengue, most patients presented with headache, disorientation, convulsion, and vomiting. The clinical diagnosis was aseptic meningitis, dengue encephalitis, cerebellitis with opsoclonus, and dengue-associated vasculitis.The imaging findings by MRI & CT Scan included leptomeningeal enhancement, hemorrhagic encephalitis, necrotizing encephalitis, multiple small infarcts, and diffuse white matter demyelination. In the case of COVID-19, it mainly presented with headaches, unconsciousness, convulsions, and changes in cognition. Clinical diagnoses were hypoxic encephalopathy, aseptic meningitis, encephalitis, ADEM, Brainstem encephalitis, and acute transverse myelitis. Imaging findings included features of hypoxic encephalopathy, focal CNS demyelination, diffuse white matter change.  We had seen typical features of Herpes simplex encephalitis (also included hemorrhagic encephalitis), Japanese B encephalitis, Nipah encephalitis and mumps encephalitis, pyogenic meningitis, brain abscess, deep fungal infections and Hydatid cyst.Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 138